Gasification of pine sawdust : Effect of temperature, oxygen rate and vapor - Matiauda, Mario Eugenio (2021)
Fil: Matiauda, Mario Eugenio. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales; Argentina.